Hierarchical Structures: Tailoring Surface Self‐Organization for Nanoscale Polygonal Morphology on Germanium (Adv. Mater. 21/2021). Issue 21 (26th May 2021) - Kamaliya, Bhaveshkumar; Garg, Vivek; Liu, Amelia C. Y.; Chen, Yu (Emily); Aslam, Mohammed; Fu, Jing; Mote, Rakesh G.
Abstract : Nanoscale polygons are fundamental building blocks toward hierarchical and 3D nanostructures for multifunctional nanodevices. In article number 2008668, Mohammed Aslam, Jing Fu, Rakesh G. Mote, and co‐workers demonstrate a single‐step process to manipulate the morphology of circular nanoholes via ion‐beam irradiation. Through nanoscale control over the self‐organization process dynamics on the surface of Ge, they realize highly periodic and protruding polygons.